Implikasi Etika pada Penggunaan Artificial Intelligence (AI) dalam Akuntansi Manajemen - Dzulhasni, Sahilly; Zakia, Dewi; Puspitasari, Endah Yuni; Wijaya, Lihan Rini Puspo (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
Artificial Intelligence (AI) has changed the way humans work, interact and manage data. One part of accounting work that is influenced by AI is management accounting. There is a gap between the demands for developing the capabilities of accountants in the AI era and the development of management accounting itself. The application of AI in the context of management accounting also raises several ethical issues that need to be considered. This research method uses a qualitative descriptive approach with an analysis of previous research literature being explored and explained. The research results suggest that it is important for future policymakers to ensure standardization of AI systems within the accounting paradigm to ensure high-quality systems that adhere to accounting principles and ethics. To address emerging ethical issues, it is important for organizations to involve ethicists and management accounting experts in the AI development and deployment process. This will help ensure that decisions made by AI systems adhere to widely accepted values and principles. This research provides novelty by filling a gap in the management accounting literature, exploring how AI can influence ethical practices in management accounting